Surgical Site Infection Following Cholecystectomy:Comparison of procedures performed with and without a laparoscope - Jawien, M; Wojkowska-Mach, J; Rozanska, A; Bulanda, M; Heczko, P.B. (International Journal of Infection Control, 2008)
The data were collected and reported by 25 hospitals participating in Nosocomial Infections Active SurveillanceSystem of the Polish Society of Hospital Infection. Data from about 5140 cholecystectomies were collected from January 2002 through December 2003. Among these cases there were 3056 holecystectomies withlaparoscope use. The total number of SSI following cholecystectomy was 125; 92 without laparoscope use and33 with laparoscope use. The incidence rate for SSI following cholecystectomy without and with laparoscopeuse was: 4.41% vs 1.08% respectively. Distribution of infection sites for cholecystectomy performed withoutand with laparoscope included: superficial incisional 68.5% vs 60.6%; deep incisional 23.9% vs 21.2%;organ/space 7.6% vs 18.2%. SSI risk index ranged from 0.15% for category -1 to 27.5% for risk indexcategory 3. Dominant microbes identified: cholecystectomy without laparoscope use: Escherichia.coli 23.9%,Enterococcus sp. 18.5%; with laparoscope use: Enterococcus sp. 20.4%, Klebsiella sp. 15.9%. The risk of SSIfollowing cholecystectomy performed without a laparoscope was higher than cholecystectomy performed witha laparoscope .